2019
DOI: 10.1109/jsen.2019.2895546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geometry on Sensitivity and Offset of AlGaN/GaN and InAlN/GaN Hall-Effect Sensors

Abstract: The current-and voltage-scaled sensitivities and signal-to-noise ratios (SNR) (with respect to thermal noise) of various octagonal AlGaN/GaN and InAlN/GaN Hall-effect sensors were examined in this work. The effect of metal contact lengths on sensitivity and sensor offset was evaluated. Calculations that take into account the shape of the device show that devices with point-like contacts have the highest current-scaled sensitivity (68.9 V/A/T), while devices with contacts of equal length to their non-contact si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The offset, , was held constant in the simulation at 5.5 µV and the magnitude of the induced voltage, , was held at 1 V•s/mT. Sheet density, ns, was 2.1×10 13 cm -2 , as measured experimentally for the InAlN/GaN Hall-effect sensor at room temperature [2]. It is observed that at 2-ω the output voltage increases linearly with an increase in Bo and is not affected by the magnitude of α and β.…”
Section: Case 1: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The offset, , was held constant in the simulation at 5.5 µV and the magnitude of the induced voltage, , was held at 1 V•s/mT. Sheet density, ns, was 2.1×10 13 cm -2 , as measured experimentally for the InAlN/GaN Hall-effect sensor at room temperature [2]. It is observed that at 2-ω the output voltage increases linearly with an increase in Bo and is not affected by the magnitude of α and β.…”
Section: Case 1: Simulationmentioning
confidence: 99%
“…The offset, , was held constant in the simulation at 21 µV and the magnitude of the induced voltage, , was held at 1 V•s/mT. Sheet density, ns, was 2.1×10 13 cm -2 , as measured experimentally for the Halleffect sensor at room temperature [2].…”
Section: Case 2: Simulationmentioning
confidence: 99%
“…Recently, there has been a demand for the stable Hall sensor operation at extreme temperatures [23,24] and also in harsh radiation environments as encountered in space exploration, determination of Curie temperatures of ferromagnetic materials [25], magnetic diagnosis of thermonuclear reactors [26] and current sensing in electric vehicles [27]. Emergence of new promising materials and advances in processing technologies continue to propel research on Hall sensors [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The geometry introduces an additional factor termed as the geometrical correction factor in the sensitivity or gain of the sensor. A recent work has reported geometrical correction factor of a 2DEG-based Hall sensor at room temperature [31]. However, the variation of this factor with temperature as well as field needs to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The Hall voltage ( V H ) results from the Hall effect generated by electrical current in a conductor, where the magnetic field is formed and is orthogonal to the electrical current. The most popular use of the Hall effect is in sensing (Alpert et al, 2019; Anuchin, Zharkov, Shpak, Aliamkin, & Vagapov, 2019; Ramsden, 2006). Sun et al (2016) have designed a wireless electrical current sensor, which consists of a wireless module, Hall sensor, and energy harvester.…”
Section: Introductionmentioning
confidence: 99%